ABOUT MEASURES TO PREVENT SEVERE ACUTE RESPIRATORY SYNDROME AT CHITINSKAYA PROVINCE - A. Ya. Miloserdov (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
Under existing conditions of severe acute respiratory syndrome (SARS) epidemics in South-Eastern Asia, mainly in China, a complex of organizing and preventive measures on the sanitary protection that allowed to decrease significantly the risk of SARS importation and dissemination at the territory of Chitinskaya Province has been realized.